Baheb el Cima: Kampen om repræsentationen i en egyptisk kontekst - Galal, Lise Paulsen (Academic Quarter | Akademisk kvarter, 2017)
In Baheb el Cima - The fight of representation in an Egyptian context, Lise Paulsen Galal analyses the global and the local tales which are activated within and around the movie Baheb el Cima in relation to its release in Egypt. Galal illustrates how the global and the local tales apparently converge in the movie, but do not converge outside the movie. The focus in the article is on the tale of freedom, and how this tale is encountered by tales of the nation, the minority and religion.